PENGARUH JENIS PENGENCER DAN KONSENTRASI SPERMATOZOA AYAM PELUNG TERHADAP PERIODE FERTIL TELUR AYAM ARAB - YUNI MARIANI; NI MADE ANDRI KARTIKA (GANEC SWARA, 2018)
The purpose of this experiment was to determine the interaction effects between diluent type and numbers of spermatozoa of Pelung Roosters on the fertile period in Arab hens’ eggs. The experiment was conducted using experimental laboratory method and CompleteRandomized Design (CRD) in a 2x3 factorial design.  Diluent type (J1= Physiological Saline and J2= Ringer lactate solution) was considered as first factor and numbers of spermatozoa (K1=50 million, K2=100 million and K3=150 million) as the second factor.  Each of the treatment was repeated nine times. Variables measured were is fertile period. The results showed that diluent type and numbers of spermatozoa had no significant interaction on fertile period and egg fertility.  Results of Anova showed that the type of diluent had no significant effect (P > 0.05) on fertile period.  The numbers of spermatozoa had no significant effect (P > 0.05) on  fertile period.. It can be concluded that Insemination with a 100 million of sperm cell for 21 day- egg collection gave the best egg fertility.